2022
DOI: 10.1177/17534666221091931
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the use of a high-flow nasal cannula to treat COVID-19 patients and risk factors for failure: a meta-analysis

Abstract: Background: Coronavirus disease 2019 (COVID-19) has spread globally, and many patients with severe cases have received oxygen therapy through a high-flow nasal cannula (HFNC). Objectives: We assessed the efficacy of HFNC for treating patients with COVID-19 and risk factors for HFNC failure. Methods: We searched PubMed, Embase, and the Cochrane Central Register of randomized controlled trials (RCTs) and observational studies of HFNC in patients with COVID-19 published in English from January 1st, 2020 to August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…These results are supported by previous studies which show that ROX index is a good predictor for HFNO failure. For example, Xu et al [ 23 ] after evaluating HFNC treatment in 2851 patients with COVID-19 found that patients in the HFNC failure group showed a significantly lower ROX index than those in the success group (4.9 ± 2.5 vs. 6.1 ± 2.7 (P < 0.01), respectively). This study also suggested that the high sensitivity observed in the ROX index was sufficient to detect HFNO failure in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are supported by previous studies which show that ROX index is a good predictor for HFNO failure. For example, Xu et al [ 23 ] after evaluating HFNC treatment in 2851 patients with COVID-19 found that patients in the HFNC failure group showed a significantly lower ROX index than those in the success group (4.9 ± 2.5 vs. 6.1 ± 2.7 (P < 0.01), respectively). This study also suggested that the high sensitivity observed in the ROX index was sufficient to detect HFNO failure in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in a previous meta-analysis which revealed that HFNC usage in COVID-19 patients was associated with reduced intubation and mortality rates. The results of that meta-analysis showed that the mortality rate after HFNC treatment was 0.23 (95% CI; 0.19, 0.29) while the intubation rates were 0.44 (95% CI; 0.38, 0.51) [ 23 ]. Similarly, a previous literature review evaluating the use of HFNC in COVID-19 reported that HFNC treatment could reduce the need for intubation and decrease the length of hospital stay [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ROX index can also well predict spontaneous heart failure (aHRF) associated with pneumonia in patients, so it is necessary to dynamically monitor ROX index in the early stage of HFNC application [10]. Four other meta-analyses also showed that the ROX index could guide the treatment of acute hypoxic intubation caused by COVID-19 or other causes [11][12][13][14]. However, relevant studies suggested that ROX index can be used as a new potential marker to identify patients at high risk of HFNC failure.…”
Section: Discussionmentioning
confidence: 99%
“…At the time, patients were mainly managed following the current guidelines; there was no alternative to prolonged mechanical ventilation and patient treatment relied on typical ARDS therapeutic strategies since the potential clinical benefits of combined therapy using non-invasive ventilation were not yet validated due to the potential aerosolization of the then emerging, and unknown, viral particles [ 27 ]. As elaborated in our analysis, when comparing different ED and ICU organ support strategies, no significant differences were found between the two subgroups other than the timing of endotracheal intubation, which was further performed earlier in the ED for Phenotype II.…”
Section: Discussionmentioning
confidence: 99%